2010
DOI: 10.1115/1.4002164
|View full text |Cite
|
Sign up to set email alerts
|

Instability of Pressure Relief Valves in Water Pipes

Abstract: Pressure relief valves in water pipes are known to sometimes chatter when the inlet pressure slightly exceeds the set pressure. While these devices are responsible for numerous fatigue issues in process industries, there is a relatively low number of technical publications covering their performance, especially in heavy fluid applications. The present study is intended as a contribution to the understanding of pressure relief valve dynamics, taking into account fluid-structure interactions. A series of tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…When the valve starts to open, the reaction force of the fluid on the valve disc can be defined by applying the momentum theory [37] with some assumptions which include the considering of a fixed and non-deformable control volume (Fig. 2) with neglecting the unsteady term (deformable volume) since it is has a small influence and these assumptions are supported by previous literature in [38,39], and hence we can write…”
Section: Equation Of Motionmentioning
confidence: 88%
“…When the valve starts to open, the reaction force of the fluid on the valve disc can be defined by applying the momentum theory [37] with some assumptions which include the considering of a fixed and non-deformable control volume (Fig. 2) with neglecting the unsteady term (deformable volume) since it is has a small influence and these assumptions are supported by previous literature in [38,39], and hence we can write…”
Section: Equation Of Motionmentioning
confidence: 88%
“…Misra 17 and Moussou 18 calculated the self-excited vibration of the poppet based on the characteristics of pipeline and the compressibility of the fluid, which indicates that the self-excited vibration occurs due to the coincidence of water hammer, acoustic feedback in the downstream pipe, high acoustic resistance at the control valve and negative hydraulic stiffness at the control valve.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have instead highlighted some problems relating to the singular behaviours of these devices, an issue that also concerns different types of control valves [44]. More specifically, some recent studies have shown the occurrence of instability in electronically controlled diaphragm PRVs under low-flow regimes.…”
Section: Introductionmentioning
confidence: 99%